THE COMMUNICATIVE TRANSLATION ANALYSIS OF CHILDREN’S BILINGUAL STORY BOOK MS WIZ THE SERIES ‘MS WIZ GOES LIVE’ BY TERENCE BLACKER - PUTRI, ROZI HANIFIA (Jurnal Ilmiah Mahasiswa FIB, 2013)
Indonesian people use English as their foreign language. As a matter offact, most of books, product instructions, jobs information and literary work havebeen written in English. It means that to understand the message and informationfrom English into Indonesian, it needs translation. The writer conducted ananalysis of Indonesian version in children’s storybook entitled Ms Wiz the Series‘Ms Wiz Goes Live’ based on communicative translation method. Since, thisanalysis is dealing with the children, there are two problems to be solved in thisstudy, namely: (1) what are the inappropriate terms found in Indonesian version ofChildren’s Bilingual Story Book Ms Wiz the Series ‘Ms Wiz Goes Live’ ByTerence Blacker; (2) how to analyze the inappropriate terms found in Indonesianversion of Children’s Bilingual Story Book Ms Wiz the Series ‘Ms Wiz GoesLive’ By Terence Blacker using communicative translation method based onchildren context. This study used qualitative approach since it was intended to explain theanalysis of the inappropriate terms found in Indonesian version of ‘Ms Wiz GoesLive’ using communicative translation method based on children context. Thisstudy was also categorized as a document analysis since this study used text as thedata source.  This study revealed that from 587 sentences there have been 144inappropriate sentences found in Indonesian version of Ms Wiz Goes Live;Ms WizJadi Bintang Televisi which sound awkward, confusing, taboo, and it is not appropriate with the context of the children. Especially in translating childrenliterature and generally another topic it needs translator visibility and invisibility.In this case the translator also must be loyal to the original author of the book.Furthermore, omission, addition, and revision are badly needed.   The writer suggested that  English Department students have to learnmore about translation especially abut context and culture. The writer also suggestto person who wants to conduct an analysis for children can analyse deeplyanother topic that related to the translation of children’s literature such as thetranslator of the storybook, the egocentric and the social child, adult authority,transaction and dialogue, the SL ,etc. Keywords: translation, communicative translation, translating for children’s book.